Perspectives in Comparative Literature (XXI Century. Spanish Literature and Culture, 2007)
This article, part of a journey through the history of Comparative Literature toshow the romantic roots of the desire to surpass cultural nationalism and the doubleroot of Comparative Literature: the zeal of synthesis and the internationalist spirit. Inthe presence of the romantic double-face of nationalism and internationalism urges anexamination of the theoretical-historical base and the validity of the idea of nationalcharacter, and for that there aren´t any unique solutions, Comparative Literature mustcombine a multiplicity of perspectives, avoiding methodic dogmatism and holloweclecticism. The two fundamental perspectives, whose characteristics and variants arediscussed in this article, are that which do not question the integrity of the nationalliteratures, and that which from the beginning organizes the works internationally,without taking into account linguistic borders.
Keywords: nacionalism; internacionalism; Comparative Literature